Secondary Radiation in Ion Therapy and Theranostics: A Review - Nandy, Maitreyee (Frontiers in Physics, 2021)
Ion therapy has emerged as one of the preferred treatment procedure in some selective indication of cancer. The actual dose delivered to the target volume may differ from the planned dose due to wrong positioning of the patient and organ movement during beam delivery. On the other hand some healthy tissues outside the planned volume may be exposed to radiation dose. It is necessary to determine the primary particle range and the actual exposed volume during irradiation. Many proposed techniques use secondary radiation for the purpose. The secondary radiation consists mainly of neutrons, charged fragments, annihilation photons among others and prompt gammas. These are produced through nuclear interaction of the primary beam with the beam line and the patient’s body tissue. Besides its usefulness in characterizing the primary beam, the secondary radiation contributes to the risk of exposure of different tissues. Secondary radiation have significant contribution in theranostics, a comparatively new branch of medicine, which combines diagnosis and therapy. Many authors have made detailed study of the dose delivered to the patient by the secondary radiation and its effects. They have also studied the correlation of secondary charged particles with the beam range and the delivered dose. While these studies have been carried out in great detail in the case of proton and carbon therapy, there are fewer analysis for theranostics. In the present review a brief account of the studies carried out so far on secondary radiation in ion therapy, its effect and role of nuclear reactions are given.